EP918 Transvaginal/transabdominal sonography for histological diagnosis in advanced ovarian cancer patients: a single institution prospective study. (1st November 2019) - Mascilini, F; Quagliozzi, L; Moruzzi, MC; Albanese, M; Testa, AC; Scambia, G; Fagotti, A
Abstract : Introduction/Background: Ultrasound-guided biopsy is an easy-available technique for obtaining tissue samples, rarely used in suspicious advanced ovarian cancer, in order to plan an early and adequate treatment. Methodology: Primary endpoints of the study were feasibility, safety and diagnostic accuracy of TA/TV ultrasound guided biopsy with respect to standard approach. Secondary endpoint was patients 'pain assessment during the procedure. This is an interventional prospective single centre study, approved by local IRB. From September 2018, all women admitted in our Institution for suspicious advanced ovarian cancer were consecutively enrolled. They underwent TA/TV ultrasound guided biopsy with an expert ultrasonographer. Results: Between September 2018 and March 2019, 90 women were eligible in the study but 8 (9.9%) refused to participate. 44 patients were lost before enrolment. The remaining 38 patients underwent a tentative ultrasound transvaginal/transabdominal biopsy, which was not feasible in 12 of them (29%) due to technical difficulties. In the remaining 26 successful procedures, the site of biopsy was ovarian mass in 13 (50%) patients, and peritoneum in the others (50%). Only one patient (3.8%) experienced fever (38°C) 24 hours after the procedure. Five patients (19.2%) experienced mild to moderate pelvic pain during the procedure which was controlled by oral analgesic therapy and lasted for ten minutes (two patients had VAS score 4 and three had VAS score 3). Samples were adequate for histopathological diagnosis in 25/26 (95%) cases: 20 gynaecological cancers, 3 non-gynecological cancers and 2 fibrosis. Sensitivity and accuracy of the procedure, compared to 22 biopsies obtained at time of surgery, were 90.1% and 90.1%, respectively due to 2 FN. Conclusion: TA/TV ultrasound-guided biopsy is a safe procedure, feasible in 70% of patients with suspicious primary advanced ovarian cancer, with a histological accuracy rate of 90.1%. Disclosure: Nothing to disclose.